Factors Influencing the Performance of Posyandu Cadres in Implementing Primary Health Service Integration - Indrayani, Kadek Ayu; Nopiyani, Ni Made Sri; Ani, Luh Seri (Universitas Padjadjaran, 2026)
This study analyzes the factors associated with the performance of Posyandu cadres in implementing integrated primary health care services in Buleleng Regency. Posyandu activities, as part of the primary health care integration, heavily rely on the performance of its cadres, which play a crucial role in ensuring the effectiveness of health programs at the community level. The results of the study show that education, employment status, motivation, facilities, incentives, and training are significantly associated with Posyandu cadre performance, with multivariate analysis revealing an adjusted odds ratio (aOR) of 4.029 for education, 3.543 for employment status, 5.673 for motivation, 5.612 for facilities, 9.435 for incentives, and 16.607 for training, all with significant p-values (p < 0.05). Meanwhile, factors such as length of service, knowledge, supervision, community support, and workload were not significantly associated with cadre performance. The study uses an analytical observational design with a cross-sectional approach, involving 134 Posyandu cadres from three health centers selected using multistage sampling. This research aims to provide insights into the factors influencing cadre performance in the implementation of integrated primary health care services, which can serve as a basis for policy recommendations to enhance program effectiveness. Based on these findings, it is recommended that Posyandu cadres improve the monitoring of nutritional status and health of school-age children and adolescents by involving local village officials or community leaders to strengthen the integration of health programs within the community. Keywords: Integrated primary health care service, motivation, education, training.